Caffeic Acid Derivatives Inhibit the Growth of Colon Cancer: Involvement of the PI3-K/Akt and AMPK Signaling Pathways - Chiang, En-Pei Isabel; Tsai, Shu-Yao; Kuo, Yueh-Hsiung; Pai, Man-Hui; Chiu, Hsi-Lin; Rodriguez, Raymond L.; Tang, Feng-Yao (PloS one, 2014)
The aberrant regulation of phosphatidylinositide 3-kinases (PI3-K)/Akt, AMP-activated protein kinase (AMPK) and mammalian target of rapamycin (m-TOR) signaling pathways in cancer has prompted significant interest in the suppression of these pathways to treat cancer. Caffeic acid (CA) has been reported to possess important anti-inflammatory actions. However, the molecular mechanisms by which CA derivatives including caffeic acid phenethyl ester (CAPE) and caffeic acid phenylpropyl ester (CAPPE), exert inhibitory effects on the proliferation of human colorectal cancer (CRC) cells have yet to be elucidated. CAPE and CAPPE were evaluated for their ability to modulate these signaling pathways and suppress the proliferation of CRC cells both in vitro and in vivo. Anti-cancer effects of these CA derivatives were measured by using proliferation assays, cell cycle analysis, western blotting assay, reporter gene assay and immunohistochemical (IHC) staining assays both in vitro and in vivo. This study demonstrates that CAPE and CAPPE exhibit a dose-dependent inhibition of proliferation and survival of CRC cells through the induction of G0/G1 cell cycle arrest and augmentation of apoptotic pathways. Consumption of CAPE and CAPPE significantly inhibited the growth of colorectal tumors in a mouse xenograft model. The mechanisms of action included a modulation of PI3-K/Akt, AMPK and m-TOR signaling cascades both in vitro and in vivo. In conclusion, the results demonstrate novel anti-cancer mechanisms of CA derivatives against the growth of human CRC cells. CA derivatives are potent anti-cancer agents that augment AMPK activation and promote apoptosis in human CRC cells. The structure of CA derivatives can be used for the rational design of novel inhibitors that target human CRC cells.